Tracking spinal cord injury: differences in cytokine expression of IGF-1, TGF- B1, and sCD95l can be measured in blood samples and correspond to neurological remission in a 12-week follow-up - Ferbert, Thomas; Child, Christopher; Graeser, Viola; Swing, Tyler; Akbar, Michael; Heller, Raban; Biglari, Bahram; Moghaddam-Alvandi, Arash (Journal of neurotrauma, 2017)
Neuroinflammation presumably has an important impact on the secondary phase of spinal cord injury and is regulated by pro- and anti-inflammatory cytokines. We analyzed serum levels of three different cytokines (insulin-like-growth-factor [IGF]-1, tumor growth factor [TGF]-β1, and soluble CD 95 ligand [sCD95L]), in blood samples of 23 patients admitted with acute traumatic spinal cord injury between November 2010 and July 2013 with a follow-up period of 12 weeks. Quantification was performed using Human Quantikine Immunoassays, classification of neurological impairment was performed using the American Spinal Cord Injury Impairment Scale at time of admission and after 12 weeks. After an initial drop of all three cytokine serum levels, IGF-1, TGF-β1, and sCD95L showed significantly increased serum levels during the acute and sub-acute phases. For IGF-1 and sCD95L, we could also observe significantly higher serum levels in patients without neurological improvement compared with patients who had improvement after 12 weeks. In this study, we were able to show differences in cytokine serum levels in patients with different neurological outcome. Measuring the serum level patterns of IGF-1, TGF-β1, and sCD95L might be a useful tool for prognosis in patients with neurological improvement and tracking the pathophysiology in further studies. Further, our observations might link promising therapeutic efforts in numerous animal studies and future studies in human patients.